Effectiveness of self-compassion training on hot flashes and night sweats in postmenopausal women - Simin Arab; Ahmad Borjali; Farahnaz Meschi; Alireza Kakavand; Maryam Zakerihamidi (Mashhad University of Medical Sciences, 2020)
Introduction: Approximately 80% of postmenopausal women suffer from hot flashes and night sweats. 25% of them report that these symptoms are the cause of poor quality of life. Drug treatments and hormone therapy, due to some complications and risks, are not the priority of use for the women, and they continue to spend the most of their time on keeping and taking care of other family members. This study was performed with aim to determine the effectiveness of self-compassion training on hot flashes and night sweats in postmenopausal women. Methods: This randomized clinical trial study was performed on 30 women aged 45-55 years in Tonekabon city who had natural menopause and referred in urban health centers in 2018. The subjects were randomly divided in to two groups of case and control (n=15 in each group). The experimental group received an 8-week self-compassion training program and the control group was placed on waiting list. Data were analyzed by SPSS software (version 22) and repeated measure covariance analysis. P<0.5 was considered statistically significant.   Results: The results showed a significant difference between the experimental and control groups after the intervention and follow-up regarding the frequency and severity of hot flashes and night sweats (P<0.001). Conclusion: Self-compassion training is effective on menopausal hot flashes and night sweats, so it is suggested to be included in postmenopausal care program.